Distribution of igneous rocks in China revealed by aeromagnetic data. (1st November 2016) - Xiong, Shengqing; Yang, Hai; Ding, Yanyun; Li, Zhankui; Li, Wei
Graphical abstract: Highlights: Aeromagnetic data were first applied to map the concealed igneous rocks in China. We analyzed more than 240 thousand magnetic susceptibility data points in China. Practical methods were proposed for mapping concealed igneous rocks. We renewed the boundaries of known igneous rocks and mapped concealed igneous rocks. We discussed the distribution of igneous rocks in China. Abstract: After several decades of aeromagnetic surveys, the measured data now cover nearly the entire Chinese continent and part of the China Sea. These data were first applied in this research and could provide important insights into the distribution of igneous rocks beneath the earth's surface. Because different types of igneous rocks have a magnetic difference and produce distinct aeromagnetic anomalies on aeromagnetic ΔT image with reduction to the pole or other data calculating maps. By analyzing more than 240 thousand magnetic susceptibility data points and aeromagnetic anomalies of known igneous rocks in the Chinese continent, it was determined that mafic-ultramafic rocks commonly have a high magnetic susceptibility and cause linear and strong positive aeromagnetic anomalies. Intermediate-felsic rocks have a stable and low magnetic susceptibility and show a flat gradient variation and regular shape. Volcanic rocks have large variability in regard to magnetic susceptibility and romance; therefore, the aeromagnetic anomalies are always random or show variation within a planar area and decrease rapidly when an upward continuation is applied. Following the aeromagnetic data and calculating the maps of the vertical first order derivative and the tilt derivative, and combining this information with known outcrops of igneous rocks, we renewed the boundaries of 82 known mafic-ultramafic rocks, 228 known intermediate-felsic rocks and 131 known volcanic rocks. In addition, we newly mapped concealed igneous rocks of 203 mafic-ultramafic rocks, 2322 intermediate-felsic rocks and 494 volcanic rocks. The igneous rocks can be identified as nine ultra-mafic belts, 10 mafic belts (or regions), 27 intermediate-felsic belts and eight volcanic blocks. The results indicate that the mafic-ultramafic rocks are mainly distributed in Tibet, Erenhot of Inner Mongolia and northern Qilian and the smaller zones in the western Kunlun, Tianshan, western Junggar, eastern Tibet, Maqin in Gansu and the Ailao Mountain (Mtn.) areas. The mafic rocks are mostly outcropped in northern Tibet, southwestern Sanjiang, Kangdian in Sichuan, Baise and Rongjiang in Guangxi, Yinjiang in Guizhou, Dabashan Mtn., Southern Dabie Mtn, Bangbu in Anhui, Qiemo in Xinjiang. The intermediate-felsic rocks are mainly located in the orogenic system and rarely within the craton. Volcanic rocks are widely developed in eastern and western China such as the circumference of Songliao Basin, Erlian Basin, the southern Yellow Sea - Subei Basin, Bohai Bay Basin, eastern Zhejiang, the circumference of Hainan Island, southern Sichuan - northern Yunan, central Tibet, the Bachu area in Tarim Basin, Junggar Basin and Turpan-Hami Basin.